Workshop Pengolahan Sampah Rumah Tangga Sebagai Upaya Edukasi Literasi Lingkungan Berkelanjutan Di Desa Citeluk, Pandeglang , Banten - Ekawati Rini Wulansari; Luluk Hermawati; Hilizza Awalina Zulfa Zulfa; Nur Bebi Ulfah Irawati Ulfah Irawati (Elevasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2025)
Household waste management remains a significant challenge in many regions, including rural areas. The low level of environmental literacy among the community, particularly children, is one of the main factors contributing to the lack of awareness regarding the importance of sustainable waste management. This community service program aimed to improve environmental literacy among elementary school students in Citeluk Village, Pandeglang Regency, through an educational and participatory workshop. The program was carried out in two main sessions: an environmental literacy session delivered interactively, and a practical session involving the creation of flower pots from used plastic bottles. The results showed an increase in students’ understanding of types of waste and their environmental impact, as well as basic skills in recycling plastic waste into useful items. Additionally, the activity fostered ecological awareness and creativity in utilizing waste materials. This initiative had a positive impact and has the potential to be further developed as a school- and community-based environmental education model.